Scholastic Rabbinism : A Literary Study of the Fathers According to Rabbi Nathan - Saldarini, Anthony J. (Book collections on Project MUSE., 2020)
"Scholastic Rabbinism is a study of two early rabbinic documents, Pirke Avot and the Avot d'Rabbi Natan. Saldarini's study examines the literary connections between these related documents while at the same time drawing larger conclusions about their provenance and what they contribute to our understanding of early rabbinic scholasticism"--Provided by publisher